EXPLORING 3D MOLECULAR STUDIES OF DIKETOPIPERAZINE ANALOGUES ON Staphylococcus aureus DEHYDROSQUALENE SYNTHASE USING GLIDE-XP - Santoso, Broto (Pharmacon: Jurnal Farmasi Indonesia, 2012)
There is a strong correlation between 3D molecular docking result with dehydrosqualene synthase protein and antibacterial activity against Staphylococcus aureus (S. aureus) of the pyrazoline analogues. The enzyme has been known as important protein for the synthesis of staphyloxanthin in S. aureus. Diketopiperazine analogues have similar structure to pyrazoline. Glide-XP, Schrodinger application that seeks for molecular docking screening between ligand and protein target is designed for speed, efficiency, and accuracy to conduct discovery efforts. The research report the three-dimension molecular studies diketopiperazine analogues for their antibacterial activity on dehydrosqualene synthase of S. aureus using Glide-XP. Analogues compound of diketopiperazine and curcumin has been calculated their geometry optimization using Gaussian-Density Functional Theory method. These 3D-optimized ligands along with reference ligands obtained from bindingDB database, MIMICs fingerprint shape screening and the compound from previous research were performed on dehydrosqualene synthase (2ZCO) for their docking score. The lowest values docking score were analyzed with multiple linear regressions. The results suggest that the diketopiperazine framework is a prospective template for modification and optimization to accomplish better potency of antibacterial activity in laboratory testing.Â Keywords: diketopiperazine, Glide-XP, docking score, Staphylococcus aureus, multiple linear regression.